1967
DOI: 10.1530/acta.0.0540328
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Pituitary-Adrenal Response to Acute Stress in Alloxan Diabetes

Abstract: The adrenal ascorbic acid depletion parameter was used to determine the pituitary-adrenal response to acute stress, the adrenal responsiveness to exogenous corticotrophin (ACTH), and the pituitary ACTH reserve in alloxan diabetes. The pituitary-adrenal response to histamine (0.5 mg/100 g i. p.) 1 hour before sacrifice was significantly impaired in uncontrolled diabetes. Elimination of glycosuria by insulin administration (7 days) restored the response to normal though adrenal hyperplasia was still evident. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is partly due to the somewhat different reaction of the various rat strains [Applegarth, 1949] but even more to the fact that the dura tion of the diabetic state is not always taken into consideration. When, however, a comparison between the acute and chronic diabetes was made, the chronically diabetic rats often received a lower dose of alloxan in order to assure their survival [Field, 1955;Devecerski and Frawlcij, 1963;Kraus, 1967]. Thus rats with various degrees of diabetes have been compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is partly due to the somewhat different reaction of the various rat strains [Applegarth, 1949] but even more to the fact that the dura tion of the diabetic state is not always taken into consideration. When, however, a comparison between the acute and chronic diabetes was made, the chronically diabetic rats often received a lower dose of alloxan in order to assure their survival [Field, 1955;Devecerski and Frawlcij, 1963;Kraus, 1967]. Thus rats with various degrees of diabetes have been compared.…”
Section: Resultsmentioning
confidence: 99%
“…The studies of Scum and Cliernick [1960) clearly demonstrated the importance of the glucocorticoids in regard to ketosis in insulin-deficient rats. On the other hand, Kraus [1967) reported that the piluary-adrenal response to stress was impaired in alloxan diabetes. Thus the possibility cannot be ruled out that changes in the adrenocortical activity during the chronic metabolic stress of uncontrolled diabetes may be causally correlated with changes in ketosis.…”
mentioning
confidence: 99%
“…Insulin effect on inflammation is of particular interesting in relation to complications in diabetes. The chronic metabolic stress of uncontrolled experimental diabetes has been reported to cause adrenal hyperactivity and hyperplasia accompanied with an increase in the plasma corticosterone level (Field, 1955;Devecerski and Frawley, 1963;Kraus, 1967).…”
Section: Discussionmentioning
confidence: 99%